Management of aggressive fibromatosis - Zhang, Zhijun (Oncol Lett, 2021)
Aggressive fibromatosis or desmoid tumor is a rare disease resulting from fibroblasts which do not metastasize. However, desmoid tumors belong to low-grade malignant tumors since they have high potential to infiltrate surrounding tissues, causing high local recurrence rates and may affect surrounding organs, threatening life quality and expectancy. Although surgery, watch and wait, radiotherapy, chemotherapy, high intensity focused ultrasound, ablation techniques or several agents have all been frequently investigated for the treatment of this type of disease, none are deemed as standard therapy for high recurrence rates that have been supported by any data. The present review retrieved literature on treatment options for desmoids to summarize the latest treatment modalities and refine their efficacy, as well as their side effects, in order to provide a more comprehensive treatment reference for clinicians.